2008
DOI: 10.2337/dc08-0333
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Onset of Disturbed Eating Behavior in Adolescent Girls With Type 1 Diabetes

Abstract: OBJECTIVE -The purpose of this study was to identify predictors of the onset of disturbed eating behavior (DEB) in adolescent girls with type 1 diabetes.RESEARCH DESIGN AND METHODS -In this prospective study, participants completed the Children's Eating Disorder Examination interview and self-report measures at baseline and at four follow-up assessments over 5 years. Participants were 126 girls with type 1 diabetes, aged 9 -13 years at baseline. Of the 101 girls who did not have DEB at baseline, 45 developed D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 32 publications
10
107
3
3
Order By: Relevance
“…335,336 Many adolescents report weight and body shape concerns, unhealthy weight control behaviors, diminished self-worth, and depression. [337][338][339] Disturbed eating behaviors are more prevalent with increased BMI 335,336 and with the perception of being overweight. 340 Disturbed eating behaviors, coupled with unhealthy weight control behaviors, have been associated with adverse glucose control.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…335,336 Many adolescents report weight and body shape concerns, unhealthy weight control behaviors, diminished self-worth, and depression. [337][338][339] Disturbed eating behaviors are more prevalent with increased BMI 335,336 and with the perception of being overweight. 340 Disturbed eating behaviors, coupled with unhealthy weight control behaviors, have been associated with adverse glucose control.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Insulin therapy leads to weight gain which can result in subsequent emotional distress, which can initiate disordered eating behaviours such as binge eating or insulin omission [43]. Amongst girls with T1DM and comorbid ED 35% of the variance has been explained by lower self-esteem and higher BMI scores [44] Similar research with people with T1DM has found DEB is significantly predicted by weight and shape worries, higher depression rates, higher BMI scores and lower appearance-based self-worth (p <0.001) [45]. These factors accounted for 48.2% of variance, offering support for the dual pathway model Olmsted et al, Daneman et al [46] FIGURE 1 and Pinhas-Hamiel et al [47] specify that T1DM specific factors interact with individual, family and social risks to lower the threshold for an ED.…”
Section: Models Of Comorbidity Of Ed and T1dmmentioning
confidence: 96%
“…Clinicians working with adolescent and young adult women diabetes should be cognizant of patterns that might indicate the presence of DEB in their patients. They can include extreme concerns about weight and body shape, unusual patterns of intense exercise, sometimes accompanied or followed by frequent hypoglycemia, unusually low-calorie meal plans, unexplained elevations in HbA1c values, repeated problems with diabetic ketoacidosis and amenorrhea (Olmsted et al, 2008). Recently, Markowitz et al (Markowitz et al, 2010) proposed a 16-items diabetes-specific self-reported measure of disordered eating for brief screening tool for disordered eating in diabetes.…”
Section: Preventionmentioning
confidence: 99%